Perancangan Aplikasi Pengamanan Pesan Chatting Menggunakan Solitaire Chiper Berbasis Android - Tiara Andini (Bulletin of Information Technology (BIT), 2021)
Progress on the delivery of android-based information has many advantages, especially because it can reduce many things that are not necessary or can be said to have an impact on efficiency in many ways. However, along with negative aspects also occur, such as crime, which includes theft, fraud and extortion. By using the Solitaire Cipher Algorithm which is a classic cryptographic algorithm, which uses playing cards as intermediaries. This type of algorithm uses the order of playing cards as keys that will be securely given to the recipient of the ciphertext. Whereas to do the encryption and decryption process of this solitaire algorithm, the order of cards is changed in certain order and rules. The design of this application also facilitates the process of securing text so that it is not easily read by others so that the authenticity of the data is maintained. It is an effort to safeguard information from those who are not entitled to access or in other words a confidential information that may not be accessed by others and may only be accessed by those who are granted access..